Optimasi Penentuan Rute Distribusi Air Minum Dalam Kemasan dengan Algoritma Clarke & Wright Saving Heuristic dan Sequential Insertion (Studi Kasus: Depot PT. Sariguna Primatirta Tbk) - Israh, Israh; Isharyani, Muriani Emelda; Utomo, Dutho Suh (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Distribution is a key activity in the supply chain as it is directly related to product delivery to customers. PT Sariguna Primatirta Tbk, the producer of Cleo bottled drinking water, distributes 19-liter gallons from its Samarinda depot using a single vehicle with a maximum capacity of 100 gallons. However, fluctuating demand often leads drivers to choose routes based on perceived shortest distance, which may cause inefficient fuel usage. This study applies the Vehicle Routing Problem approach using the Clarke & Wright Saving Heuristic and Sequential Insertion algorithms. The results show that the Sequential Insertion algorithm reduced the total distance to 294.70 km, achieving fuel savings of Rp57.400.00 (16.30%). In comparison, the Clarke & Wright Saving Heuristic reduced the distance to 320.10 km with fuel savings of Rp32.000.00 (9.09%).